Towards a density of states approach for dense matter systems - Biagio Lucini (2013)
The density-of-states method (Phys.Rev.Lett. 109 (2012) 111601) features an exponential error suppression and is not restricted to theories with positive probabilistic weight. It is applied to the SU(2) gauge theory at finite densities of heavy quarks. The key ingredient here is the Polyakov line probability distribution, which is obtained of over 80 orders of magnitude. We briefly address whether the exponential error suppression could be sufficient to simulate theories with a strong sign problem.